Pelvic pseudocyst presenting with vaginal drainage of cerebrospinal fluid in an adolescent: A rare complication of ventriculoperitoneal shunt - Nancy Nimer; Robin T. Petroze; Kathryn LaRusso; Jean-Pierre Farmer; Pramod Puligandla (Journal of Pediatric Surgery Case Reports, 2020)
The case report describes a 16-year-old female with a ventriculoperitoneal (VP) shunt due to congenital hydrocephalus. She presented with abdominal pain and vaginal leakage of cerebrospinal fluid (CSF). CT imaging demonstrated multiple intra-abdominal and pelvic CSF pseudocysts as well as possible erosion of the VP shunt into the vagina. She was taken to the OR for externalization of the shunt and resection of pseudocysts. Surprisingly, the VP shunt tubing was not related to the vagina at all. Instead, there was a large, inflamed pseudocyst within the pelvis and CSF was draining through the fallopian tubes which were located within it. This cyst was only partially resected to protect the fallopian tubes and surrounding structures. Post-operatively, cultures of the CSF demonstrated an infection by Propionibacterium, pathogens that form part of the normal skin flora, but rarely of the vaginal flora in adolescent girls (Huang et al., 2014) [1]. Vaginal drainage stopped and the patient made a full recovery. This case highlights the very rare finding of a CSF pseudocyst decompressing through the fallopian tubes and provides an overview of the complications associated with VP shunts.